2014
DOI: 10.1007/s11096-014-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

A modified busulfan and cyclophosphamide preparative regimen for allogeneic transplantation in myeloid malignancies

Abstract: The new regimen was associated with a low relapse rate, low incidence and severity of graft versus host disease and satisfactory survival for patients with myeloid malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The high TRM in the alloHSCT group is largely attributable to early mortality. Despite advances in supportive care, and the procedure of alloHSCT improved, the high rate of early mortality is still an important limitation for alloHSCT[ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high TRM in the alloHSCT group is largely attributable to early mortality. Despite advances in supportive care, and the procedure of alloHSCT improved, the high rate of early mortality is still an important limitation for alloHSCT[ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan (Bu) is a bifunctional alkylating agent routinely used in preparative regimens prior to hematopoietic stem cell transplantation (HSCT) in treatment of various malignancies and inherited disorders . It is a cell cycle nonspecific agent which can ablate bone marrow, and is usually used in combination with other cytotoxic drugs, such as cyclophosphamide, fludarabine . In vivo studies have shown that the pharmacokinetics of busulfan is adequately described by one compartment open model with a half‐life of 2‐3 hours .…”
Section: Introductionmentioning
confidence: 99%
“…9 Over the past 15 years, several HSCT centers have personalized either oral or intravenous Bu using therapeutic drug monitoring (TDM), and TDM has been the standard of care for HSCT patients in these centers. 13 It has been recommended [14][15][16][17][18] that an area under the plasma concentration vs time curve from 0 to 6 hours (AUC [0][1][2][3][4][5][6] of busulfan should between 900 and 1500 μmol/L/min. AUC 0-6 lower than 900 μmol/L/min is associated with engraftment failure, 16,18 while AUC 0-6 higher than 1500 μmol/L/min results in hepatic veno-occlusive disease.…”
mentioning
confidence: 99%
“…Moreover, even if we had not identified this pathway in our in silico analysis of the RNAseq data, it was described that an increase in lipid peroxidation was observed in busulfan-treated testes after 1–2 weeks [ 22 ], suggesting an increase in reactive oxygen species (ROS) production. Indeed, mice treated with melatonin after busulfan injection showed enhanced spermatogenesis [ 23 ], and melatonin drives the expression of MnSOD (manganese superoxide dismutase), which counteracts apoptosis caused by high levels of busulfan-induced ROS [ 24 ].…”
Section: Resultsmentioning
confidence: 99%